Arteriovenous malformation underlying a plexiform neurofibroma: An unusual presentation - Zaheer Abbas; Sepideh Khani; Javad Zare (Wolters Kluwer Medknow Publications, 2017)
Vascular abnormalities associated with neurofibromatosis type 1 are well described in the literature, however, arteriovenous malformation is a very rare finding in neurofibromatosis type 1. We report the case of an 11-year-old girl who presented with a soft mass on the right flank. Provisional diagnosis of plexiform neurofibroma was made on the basis of clinical and histological observations. Because the lesion was warm on palpation, imaging studies were performed to evaluate further and arteriovenous malformation was detected underlying the plexiform neurofibroma. This report emphasizes the importance of careful examination and proper investigations of the plexiform neurofibroma prior to treatment strategies to avoid future complications. The rarity of plexiform neurofibroma in association with arteriovenous malformation at the same site was also highlighted in this report.